Developing Educational Game Application Toward Students’ Alphabet Understanding for Kindergarten Students Through Android Application: English - Ukhtul Iffah; Nofa Rifqiyanti (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
Given the dearth of resources for teaching and learning about alphabet comprehension, the goal of this project was to create instructional gaming applications for kindergarten children using Android applications. Research and development (R&D) was done for this project. Students from RA Darul Hidayah in Kangean Sumenep, East Java, served as the study's subjects. Research procedures included developing a media product, getting expert validation, testing the product, and having a teacher evaluate it. Steps for testing the product were twice. Fifteen students participated in the first tryout, while sixteen students participated in the second. Expert validation of the creation of educational game applications led to the conclusion that testing was highly appropriate. Based on the findings of two tests, it was determined that this product was extremely appropriate for implementation. The first test produced a total result of 665 with an 88% percentage, classifying it as very proper, and the second test produced 750 with a 93% percentage, also classifying it as very proper.